The preclinical teaching of the “Chairside Economical Restoration of Esthetic Ceramic” workflow: A questionnaire-based evaluation - Maximilian Nothaft; Eva Groth; Eichhorn Tim; Mihai Rominu; Ruediger Junker (Saudi Journal of Oral Sciences, 2023)
Introduction: As part of the preclinical teaching of computer-aided design (CAD) and computer-aided manufacturing (CAM) systems at Danube Private University (DPU) the Chairside Economical Restoration of Esthetic Ceramic (CEREC) system is introduced in the third semester, using the so-called CEREC curriculum. Here, the students learn about the use of the CEREC system for scanning their dental preparations in the phantom head and designing fixed dental prostheses. Aims: The perspective and feedback of students is essential for the success of teaching modules, which is why their views on the so-called curriculum CEREC (CAD/CAM) were evaluated using an anonymous questionnaire. Materials and Methods: A survey study in written form was conducted using anonymized questionnaires. A descriptive statistical analysis of the ratings of the statements in the questionnaires in Microsoft Excel and IBM followed this SPSS statistics (version 27). Results and Discussion: The results show that the curriculum CEREC was predominantly positively evaluated, and the learning content was positively received. The training of the assessment ability, as well as the promotion of motivation in the course of study, the acquisition of a better understanding, and optimized self-assessment through CEREC could also be affirmed. Conclusion: However, it could be concluded that, according to the students, the use of a CEREC system could not replace the feedback of a lecturer.